Janus Nanobullets Combine Photodynamic Therapy and Magnetic Hyperthermia to Potentiate Synergetic Anti‐Metastatic Immunotherapy. Issue 22 (12th September 2019) - Wang, Zheng; Zhang, Fan; Shao, Dan; Chang, Zhimin; Wang, Lei; Hu, Hanze; Zheng, Xiao; Li, Xuezhao; Chen, Fangman; Tu, Zhaoxu; Li, Mingqiang; Sun, Wen; et al.
Abstract: Photodynamic therapy (PDT) is clinically promising in destructing primary tumors but ineffective against distant metastases. This study reports the use of immunogenic nanoparticles mediated combination of PDT and magnetic hyperthermia to synergistically augment the anti‐metastatic efficacy of immunotherapy. Janus nanobullets integrating chlorine e6 (Ce6) loaded, disulfide‐bridged mesoporous organosilica bodies with magnetic heads (M‐MONs@Ce6) are tailored for redox/pH‐triggered photosensitizer release accompanying their matrix degradation. Cancer cell membrane cloaking enables favorable tumor‐targeted accumulation and prolonged blood circulation time of M‐MONs@Ce6. The combination of PDT and magnetic hyperthermia has a strong synergy anticancer activity and simultaneously elicits a sequence of immunogenic cell death, resulting in synergistically tumor‐specific immune responses. When combined with anti‐CTLA‐4 antibody, the biomimetic and biodegradable nanoparticle enables the notable eradication of primary and deeply metastatic tumors with low systematic toxicity, thus potentially advancing the development of combined hyperthermia, PDT, and checkpoint blockade immunotherapy to combat cancer metastasis. Abstract : Janus magnetic nanoparticles are designed for redox‐/pH‐triggered photosensitizer release accompanying their matrix degradation. Cancer cell membrane cloaking improves combined photodynamic therapy and magnetic hyperthermia in a remarkable anticancer manner, which is harnessed for synergistic tumor‐specific immune response to integrate with cytotoxic T lymphocyte‐associated antigen‐4 antibody for notable eradication of primary and metastatic tumors with low systematic toxicity.